2010
DOI: 10.1016/j.ymgme.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late treatment of spinal cord compression with long-term intrathecal enzyme replacement therapy in canine mucopolysaccharidosis type I

Abstract: Enzyme replacement therapy (ERT) with intravenous recombinant human alpha-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 23 publications
0
42
1
2
Order By: Relevance
“…All therapeutic studies were preapproved by the Institutional Animal Care and Use Committee and adhere to the ARVO Statement for the Use of Animals in Ophthalmic and Vision Research; further details concerning these animals have been reported elsewhere. [17][18][19][20][21][22] …”
Section: Animal Informationmentioning
confidence: 99%
“…All therapeutic studies were preapproved by the Institutional Animal Care and Use Committee and adhere to the ARVO Statement for the Use of Animals in Ophthalmic and Vision Research; further details concerning these animals have been reported elsewhere. [17][18][19][20][21][22] …”
Section: Animal Informationmentioning
confidence: 99%
“…Enzyme replacement therapy (ERT) has also been able to stabilize the visceral manifestations of both MPSIH and MPSII, but its lack of ability to cross the blood-brain barrier (BBB) has prevented successful treatment of the neurologic aspects of these diseases through intravenous infusions of enzyme (4,6 ). Recently, the delivery of these enzymes through an intra-thecal route has been explored as a means of improving neurological outcomes (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Reports of trials with IT ERT in MPS I and VI animals as well as MPS I patients have also been described [17,18,19,20,21]. The use of the drug in the canine model of MPS I with CNS manifestations resulted in achieving very high enzyme levels and a noticeable reduction of GAG storage in the spinal meninges after 4 weekly doses [17].…”
Section: Discussionmentioning
confidence: 99%
“…The use of the drug in the canine model of MPS I with CNS manifestations resulted in achieving very high enzyme levels and a noticeable reduction of GAG storage in the spinal meninges after 4 weekly doses [17]. Other animal studies showed that IT ERT can diffuse widely throughout the CNS and treat disease there effectively [19,20,21], and reduction in stored material, improved histopathology, longer lifespan and neurobehavioral improvement has been also observed [20,22]. IT drug administration is an established route for treatment of disorders such as chronic pain (due to cancer or other conditions) and spasticity.…”
Section: Discussionmentioning
confidence: 99%